The association between vocabulary size and language dominance of bilingual Malay-English undergraduates - Rahman, Arifur; Yap, Ngee Thai; Darmi, Ramiza (Penerbit Universiti Kebangsaan Malaysia, 2018)
Bilingual learners' inadequate English vocabulary size is one of the most frequently stated problems in applied linguistics. Using mostly qualitative case studies, earlier findings reported several factors (e.g. negative attitude, lack of exposure, poor proficiency, and age of acquisition) as related to bilingual learners’ insufficient English vocabulary size. Therefore, the present study undertakes an in-depth quantitative study to measure language dominance, which encompasses language history, use, proficiency, and attitude towards Malay, the first language (L1), and English, the second languages of 96 Malay-English bilingual undergraduates. It also examines the relationship between vocabulary size and overall dominance scores. The 20,000 Vocabulary Size Test was used to measure English vocabulary size and the Bilingual Language Profile (BLP) was used to determine the dominance score. The results show that most of the Malay-English bilinguals are Malay dominant. A positive and statistically significant association was found between the overall language dominance score and English vocabulary size. One of the most striking findings to emerge from this study is that the language dominance score accounts for 30% of the variability in the vocabulary size of Malay-English undergraduates.